EKRANISASI NOVEL DIA ANGKASA KARYA NURWINA SARI YANG DISUTRADARAI ADHE DHARMASTRIYA - Suci Ramadhani Putri; Mangatur Sinaga; Elmustian (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the ecranization of the novel Dia Angkasa by Nurwina Sari into the web series Dia Angkasa directed by Adhe Dharmastriya, focusing on the aspects of plot, characters, and setting. The background of this research is driven by the popularity of the novel, which reached over 8 million readers on Wattpad, and its subsequent adaptation into a modern audiovisual format like a web series. This research uses a qualitative descriptive method with an ecranization theory approach by Pamusuk Eneste. Data were collected through reading, taking notes, and observing the web series episodes. The results showed significant changes in three aspects: reduction, addition, and varied changes. In the plot aspect, 32 reductions, 22 additions, and 15 varied changes were found. Regarding characters, there were 16 reductions, 7 additions, and 1 varied change. In the setting aspect, the study identified 12 reductions, 7 additions, and 3 varied changes. These transformations occur due to medium differences, duration constraints, and the director's creative interpretation to make the story more visually appealing and dramatic while maintaining the original essence of the literary work.